Perbandingan Return dan Risiko Saham Subsektor Perbankan dengan Subsektor Property Real Estate yang Terdaftar di BEI - Ladysa Awala; Tjetjep Djuwarsa; Dimas Sumitra Danisworo (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
The Indonesia Stock Exchange (IDX) noted the rise investors during 2019. In addition, some of the sector on the market capital shows the rapid development. It can be seen from a stock transactions. However, the developments is not indicate the return and risk of every sector. This research aims to determine differences in return and risk of stock between banking subsector and property, real estate subsector on the period 2019. The data used are secondary data obtained from Indonesia Stock Exchange and Id Investing. The research sample used was of 16 (sixteen) companies stock in the banking subsector and 14 (fourteen) companies stock in the property, real estate. This study used the Mann Whitney Test using SPSS version 24 software as analysis tool. The result of this research shows that there is no significant difference return and risk between banking subsector and property, real estate subsector.